A proposed program for the correction of promiscuous spitting among the intermediate pupils of Bais City public schools - Galera, Pura Adalid 1947-
The study seeks to propose a program for the correction of promiscuous spitting among the intermediate pupils of Bais City Public Schools. Using the normative survey, a health questionnaire of the check list type was utilized in gathering the needed data. The proposed program consists of four phases, namely: Health Instruction, Health Services, Healthful Living and Schooling Community Coordination.